PENGARUH LEVERAGE, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN AKTIVITAS TERHADAP PROFITABILITAS PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saputra, Dasriyan; Ardiles, Alief (Jurnal GeoEkonomi, 2024)
This research aims to determine the effect of Leverage (Debt to Equity Ratio), Firm Size, Sales Growth and Activity (Total Asset Turnover) on Profitability (Return On Assets). This research is quantitative research. The population in this study are Property and Real Estate sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique in this research is Purposive Sampling. The research sample was 11 companies and the total population was 37 companies. The data analysis techniques used are Descriptive Statistical Test, Classic Assumption Test, Multiple Linear Regression Test and Hypothesis Test assisted by the SPSS 25 program. The results of this research show that partially the Debt to Equity Ratio (DER) has a negative and significant effect on Return On Assets (ROA), Firm Size (FS) has a negative and significant effect on Return On Assets (ROA), Sales Growth (SG) has no negative and insignificant effect on Return On Assets (ROA) and Total Asset Turnover (TATO) has a positive and significant effect on Return On Assets (ROA). Simultaneously, the variable Debt to Equity Ratio (DER), Firm Size (FS), Sales Growth (SG) and Total Asset Turnover(TATO) have a positive and significant effect on Return On Assets (ROA).